2018
DOI: 10.1097/rnj.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Caregivers of Individuals With Parkinson’s Disease

Abstract: Rehabilitation nurses should identify caregivers at high risk in order to improve their quality of life. Nurses should assess education program needs and caregiving appraisal of caregivers of individuals with Parkinson's disease and develop a customized intervention program.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…For this purpose, they sought support in social interactions and conversations, recreational activities like book reading or listening to radio. This is in congruence with prior research, which has majorly highlighted the significant role of conversations and social support as key mechanisms to cope with the caregiver stress and preserve their self-identity (Abendroth et al, 2012 ; Lee et al, 2019 ; Smith & Shaw, 2017 ). However, as proposed by Yalom ( 2000 ), in the face of uncertainty, faith and meaning in the greater scheme of things, often acts as a support mechanism.…”
Section: Discussionsupporting
confidence: 88%
“…For this purpose, they sought support in social interactions and conversations, recreational activities like book reading or listening to radio. This is in congruence with prior research, which has majorly highlighted the significant role of conversations and social support as key mechanisms to cope with the caregiver stress and preserve their self-identity (Abendroth et al, 2012 ; Lee et al, 2019 ; Smith & Shaw, 2017 ). However, as proposed by Yalom ( 2000 ), in the face of uncertainty, faith and meaning in the greater scheme of things, often acts as a support mechanism.…”
Section: Discussionsupporting
confidence: 88%
“…The number of studies on care recipient behavioural problems ranked highest (8 studies) Harwood, Ownby, Burnett, Barker, & Duara, 2000;Kramer, 1997;Liu & Huang, 2018;Pruchno & Patrick, 1999;Rapp & Chao, 2000;Smith, Onwumere, Craig, & Kuipers, 2018;Verbakel et al, 2018), among which five were on dementia, followed by patients with chronic disabilities (1 study), the general older adults (1 study) and psychosis (1 study). Seven studies were on care recipient functional status (Harvey, Burns, Fahy, Manley, & Tattan, 2001;Keir, Farland, Lipp, & Friedman, 2009;Liu & Huang, 2018;Pruchno & Patrick, 1999;Tsai & Pai, 2016;Verbakel et al, 2018), including social functioning and physical functioning, and care recipient disease severity (4 studies) (Kramer, 1997;Lee, Kim, Kim, Kim, & Sohn, 2018;Tsai & Pai, 2016;Yamamoto-Mitani et al, 2003).…”
Section: Factors At the Individual Levelmentioning
confidence: 99%
“…As an important factor in Lazarus model (Lazarus & Folkman, 1984), caregiver's coping strategies were closely related to caregiving appraisal (Chronister et al, 2010;Hanks, Rapport, & Vangel, 2007;Kramer, 1997;Parks, Anastasiadou, Sanchez, Graell, & Sepulveda, 2018). Caregiver's use of social service and quality of life were also associated factors (DiBartolo & Soeken, 2003;Gupta & Bowie, 2018;Lee et al, 2018;Yamamoto-Mitani et al, 2003).…”
Section: Factors At the Individual Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale was used with the original author's approval. The original study reported a Cronbach's α of 0.93 (O. Kim, ) and a previous study examining family support from caregivers of people with PD in Korea reported a Cronbach's α of 0.91 (J. Lee, Kim, Kim, Kim, Kim, & Sohn, ). In the present study, Cronbach's α was 0.96.…”
Section: The Studymentioning
confidence: 99%